Fortification and Utilization of Local Food Rich in Vitamin A (Yellow Pumpkin) for Stunting Prevention in South Sumatra - Putra, Nico Syah; Azzahra, Siti Aisyah; Jaya, Okta Pranata; Anantasya, Galuh Mutia; Taufiq, Muhammad; Sari, Bela Indria (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Stunting remains a major nutritional problem in Indonesia, including in South Sumatra, which is influenced by low vitamin A intake. Yellow pumpkin (Cucurbita moschata), as a local food rich in β-carotene, has the potential to be a sustainable source of provitamin A. This review analyzes the scientific evidence on the role of vitamin A in child growth and the effectiveness of yellow pumpkin fortification as a stunting prevention strategy. Literature search was conducted using the PRISMA approach on PubMed, ScienceDirect, and Google Scholar. Ten relevant articles were reviewed to assess biological aspects, nutritional composition, processing technology, and implementation challenges. The results showed that yellow pumpkin fortification improved the provitamin A content and nutritional quality of the product without decreasing sensory acceptability, with the best β–carotene retention through steaming and light roasting. In South Sumatra, the abundant availability of raw materials and low production costs support the implementation of local food-based fortification. However, evidence on the direct impact on vitamin A status and linear growth is still limited so further research is needed. Overall, yellow pumpkin fortification is a potential and sustainable approach to support efforts to accelerate stunting reduction.